Religious Motifs in Soviet Prose by M. Sholokhov (Story “Family Man”) - O. V. Bogdanova; T. N. Baranova (Научный диалог)
A new interpretation of Mikhail Sholokhov’s story “Family Man” from the collection of stories “Lazorevaya Step” (“Don Stories”) is proposed. Traditionally, the image of the central character — the Cossack ferryman Mikishara — has been interpreted as a portrayal of a sinful hero, a criminal, a patricide. However, the author of the article considers the leading character’s image in light of biblical motifs and parallels. It is demonstrated that the old ferryman’s night confession is permeated with allusions to sacred biblical texts, specifically to the image of God the Father who sent his own Son to death. The image of the Cossack father is constructed by the writer in projection to the sacred image of the Father-Spirit, and in this comparison, new semantic markers of the character’s nature are explicitly revealed. The temporal constant of the confessional narrative — Easter — is supplemented by Sholokhov with motifs such as dove, soul, willow, river, fish, and others. Thus, an unexplored layer of meaning in the work emerges in which new components of the motif system begin to appear: not sin and guilt, but misfortune and sacrificialness, torment and suffering that the Cossack-father faced in the conditions of a terrible fratricidal civil war. The analysis demonstrates how the poethological components of the story (title, change of title, composition “story within a story”, plot dynamics and narrative pauses, symbolized landscape, portraiture techniques, etc.) are oriented by the writer towards authorial evaluative meanings.